Future anxiety among students of the Faculty of Education at Tishreen University In light of some variables - صبح, صفاء; ليفا, رهام (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This study aims to know the level of future anxiety among students of the Faculty of Education, Tishreen University, and to know the differences between students in the level of future anxiety according to gender, specialization, and academic year. The sample of the study consisted of (312) male and female students, including (78) male and (234) female students, distributed over the first and last years in university. The results of the study showed that there is an average level of future anxiety in the study sample, and showed that there is an average level of future anxiety among the study sample. The results also showed that there were no statistically significant differences between the sample members in the level of future anxiety due to the gender variable and specialization (psychological counseling, curricula, class teacher). While the results revealed a statistically significant difference in the level of future anxiety attributable to the variable of the school year in favor of students of the last year (graduation).